International trade and recovery strategies in Kenya in the context of COVID-19 - Kiriti-Nganga, Tabitha (AOSIS, 2022)
COVID-19 led to an economic downturn not only in Kenya but also in the rest of the world. It put these countries into a recession as a result of the measures taken by trading partners to prevent the spread of the virus. This meant that the Kenyan needed to come up with monetary and fiscal policies and strategies to maintain macroeconomic and fiscal stability, as well as accelerate the pace of economic growth by achieving resilience and sustainability of economic growth and development. This book uses both descriptive and econometric methodologies that can easily be understood by scholars, using quality data from credible sources such as the Kenyan National Bureau of Statistics, the Ministry of Health, World Bank, World Trade Organization and the International Monetary Fund. The book can be used as reference material for both post and undergraduate students interested in international trade. The policies and strategies proposed can be used by scholars in researching ways to deal with not only the current pandemic but also future pandemics.